Stakeholder Perceptions Among School Nutrition and Mid-Day Meal Programme - Joshi, Hari Prasad; Bohara, Kishore (Journal of Research in Education, 2025)
The midday meal program is a key initiative that aims to improve school-aged children’s health, nutrition, and education. This study carried out in a basic school in Gulariya Municipality, Bardiya District, Nepal, investigates the perspectives and experiences of students, parents, teachers, and the school management committee on the program. Data were obtained using a qualitative case study design based on social cognitive theory, with focus group discussions and in-depth interviews to understand better the dynamic interplay between individual, behavioural, and contextual factors. The findings emphasize the program’s beneficial effects on students’ health, attendance, and learning outcomes. Despite these advantages, major obstacles to implementation exist, including insufficient finance, inadequate infrastructure, limited human resources, and concerns about the quality, quantity, and variety of food. The program’s short length reduces its potential. These limitations are consistent with broader issues raised in global research on school-based lunch programs, but they are exacerbated by Nepal-specific variables such as resource restrictions and cultural considerations. To maximize the program’s benefits, stakeholders must address these concerns by boosting financing, enhancing facilities, and encouraging greater community and policymaker collaboration. By overcoming these challenges, the mid-day meal program can continue to contribute to the overall development and well-being of school children, ensuring its long-term viability.